2008
DOI: 10.1210/en.2008-1048
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 9 Is a Germ Cell Regulator of Sertoli Cell Function

Abstract: Oocyte-secreted growth differentiation factor (GDF) 9 and bone morphogenetic protein (BMP) 15 are critical regulatory factors in female reproduction. Together, they promote granulosa cell proliferation and stimulate the maturation of preovulatory follicles. Despite their importance in female fertility, GDF9 and BMP15 expression patterns and function during spermatogenesis have not been investigated. In this study we show that the expression and stage-specific localization of both factors are limited to the ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 59 publications
5
56
0
1
Order By: Relevance
“…Fitzpatrick et al (1998) and Pennetier et al (2004) detected expression of GDF9 in the testis, and suggested that it could potentially regulate testicular function. This concept is also supported by the dynamic regulation of BMPRII, ALK5, and ALK6 expression throughout the seminiferous tubules, and the fact that Smad signaling pathways are vital for the control of testis development and spermatogenesis (Itman et al, 2006(Itman et al, , 2008Nicholls et al, 2009). However, Dong et al (1996) found that GDF9-knockout males are fertile and show no gross physical or behavioral defects, which indicated that the actions of GDF9 are not essential for the initiation or maintenance of spermatogenesis.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Fitzpatrick et al (1998) and Pennetier et al (2004) detected expression of GDF9 in the testis, and suggested that it could potentially regulate testicular function. This concept is also supported by the dynamic regulation of BMPRII, ALK5, and ALK6 expression throughout the seminiferous tubules, and the fact that Smad signaling pathways are vital for the control of testis development and spermatogenesis (Itman et al, 2006(Itman et al, , 2008Nicholls et al, 2009). However, Dong et al (1996) found that GDF9-knockout males are fertile and show no gross physical or behavioral defects, which indicated that the actions of GDF9 are not essential for the initiation or maintenance of spermatogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…However, whether the action of GDF9 affects the function of tight junctions, sperm quality, including number, maturation, mobility, and viability, or the circulating concentrations of the key hormones testosterone, FSH, and inhibins has not been analyzed. Furthermore, Nicholls et al (2009) found that GDF9 can modulate key functions of Sertoli cells by affecting the function of tight junctions and the expression of inhibin B. Therefore, in this study, we aimed to elucidate the effects of GDF9 mutations on sperm quality traits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations